Cultural Diversity in Management, Firm Performance, and the Moderating Role of Entrepreneurial Orientation Dimensions - Richard, Orlando C.; Barnett, Tim; Dwyer, Sean; Chadwick, Ken (Academy of Management Journal, 2004)
Extending previous theorizing on cultural diversity's organizational effects by integrating value-in-diversity and social identity perspectives with the framework of Blau's (1977) theory of heterogeneity, we hypothesized curvilinear relationships between racial and gender diversity in management and firm performance. We evaluated relationships within the context of firm-level entrepreneurial orientation. Our empirical study indicated complex relationships among study variables. It revealed that innovativeness positively and risk taking negatively moderated nonlinear relationship patterns for both racial and gender heterogeneity. Research and practical implications are discussed.